The Popularity of Wilkie Collins’s Sensation Fiction in Spain: The Case of The Woman in White - Lázaro, Alberto (Complutense Journal of English Studies, 2022)
Wilkie Collins, one of the most popular Victorian novelists, has been widely acclaimed as the early master of the sensation novel and a pioneer of English detective fiction. Novels such as The Woman in White (1860) and The Moonstone (1868) became best sellers and captivated Victorian readers with their convoluted plots full of mystery, crime and sexuality, usually within the respectable middle-class home. His popularity crossed national and linguistic borders, and his novels, novellas and short stories were soon translated into different languages. In Spain, we find over a dozen of different editions of Collins’s stories already in the nineteenth century, which often appeared serialised in popular journals or magazines, like their original counterparts. One of these early Spanish translations was The Woman in White which, in different forms and with different titles, attracted the attention of many publishers and readers during the twentieth century, despite the obstacles posed by censorship and the hardships of the post-war period. This paper aims to discuss the Spanish publication history and reception of Collins’s sensation novel The Woman in White and analyse the scale of its popularity.